Genetic responses of traits relationship to components of nitrogen and phosphorus use efficiency in maize - doi: 10.4025/actasciagron.v35i1.15237 - Júlio César DoVale; Ciro Maia; Roberto Fritsche-Neto; Glauco Vieira Miranda; Paulo Cézar Cavatte (Acta Scientiarum. Agronomy, 2012)
This study had three objectives: i) to observe maize inbred lines response to nitrogen (N) and phosphorus (P) acquisition as well as their utilization efficiencies and traits of root morphology in contrasting levels of these nutrients, ii) to study the relationship between root morphology and nutrient use efficiencies for both nutrients, and iii) to identify contrasting parents with components N and P use efficiency for an inheritance study. We evaluated 15 inbred lines in two experiments conducted in contrasting conditions of N and P. We evaluated the shoot, root traits and nutritional efficiencies and observed the genetic variability for most traits. Selection can be practiced for most of these traits in specific environments. Under conditions of nutritional stress, average and heritability estimates were of lesser magnitude. In this study, the shoot and root morphology traits were shown to be associated with the acquisition efficiency of both N and P in all of the environments that were evaluated.